A biblioteca escolar e os nativos digitais - Raquel Miranda Vilela (2018)
Although data from the School Census point to improvements in the reality of the school library (BE), this space is not yet present in all Brazilian schools. Debates about the school library began in the 1970s, but many themes are still more in theory than in practice. The bibliography on school library shows that, although this space does not always exist, its importance is affirmed in all theories. The present thesis has as one of its assumptions that the role of the school library goes beyond the traditional training of readers. The pedagogical function of the school library should be more debated and assumed by professionals present in this space. These reflections are present in the studies on information literacy. Librarians working in school libraries, in addition to their role as educators, have to be concerned with adjusting their performance to the students to be served. Given the need of the library present in the school context to assume its pedagogical role and prepare to work with the young digital natives, the project believes that it is fundamental to know this new public, which is inserted in the Information Society and immersed in technology. For a more effective performance it is believed to be necessary to understand how these students think and deal with the library and the information. The research investigated what current students, digital natives, think about the contribution of the school library and the librarian in their training. Consequently, it was hoped that as a solution to this problem, it would be possible to present cluesand suggestions to answer the adjacent question: how should the school library be adapted to meet the expectations of these students in relation to their information services? The theoretical contribution that bases the research has points that contribute to the understand in go of the question and includes: the school library and its work in Brazil; the information al literacy and the educational role of BE, the formation and performance of the librarian in the school context and the Digital Natives. An ethnographic research was carried out. Data collection was done through field notes / field diaries and recordings. At the moment, the theories of Wolcott (1994) were used, using the description, analysis and interpretation framework for the organization and treatment of this collected information. The work was carried out in three schools, one public and two private. These schools present three distinct library realities, as well as different teaching styles. The work pointed out that these students, digital natives, have their own characteristics, as cited by Prensky (2011) and Palfrey; Gasser (2011) had al ready listed. Given these characteristics, it is concluded, among other things, that rather than changing the space of the school library, it is necessary to change the position of the librarian in this context